Água como elemento construtivo da Quinta de Valverde. Estudo e projecto - Pedro Miguel Lema Moreira dos Santos (2016)
Since time immemorial, mankind has foraged for water. Its quality and its quantity influenced the rise of many settlements and empires, and, in other cases, their demise. However, if in the early days it was the existing conditions that influenced where man would settle and raise a city, there were times where other factors played a role in where a city would be built. Cities in more inhospitable places began emerging, places where water was not easily accessible. This forced said population to extract water by utilising ingenious mechanisms that would accomplish that very same goal, as well as collect and distribute the water. In order to replace mines, as well as rivers, wells and cisterns were constructed, and they would collect the water from the underground or store rainwater, which led to a more efficient way of using it. With the growth of populations, the constant demand for water and the shortage of said resources, it became necessary to retrieve water from more distant places. It was then, that sophisticated hydraulic were developed. At first, they were simple devices, that carried water with the aid of gravity, but they quickly expanded to more complex mechanisms that would carry the water through pipes, siphons and tunnels, as well as contention measures, such as dams. All this was done before the rise of the Greek Empire. After this, the Roman Empire perfected some of these techniques, like the construction of awe-inspiring aqueducts, that transported water across vast distances. It was exactly the roman civilisation that dotted our landscape with important hydric infrastructures, that played a vital role in supplying populations with water. Amongst some of these monuments, we can highlight the aqueducts of Conímbriga and Gargantana. After the 15th century, many aqueducts were built and repaired, and it was at that time that D. João II ordered the construction of the first aqueduct, in Portugal, from scratch. In Évora, during the reign of D. João III, in 1531, the construction of the 18 kilometre-long aqueduct begun, directed by the architect Francisco Arruda. The work was concluded in 1537. This aqueduct was built in rapid response to the enormous drought that threatened the country at the time. The same thing happened in Quinta de Valverde, where not only three aqueducts were constructed, but also a complex hydraulic system that affected the local climate, the landscape and its very own architecture. These constructions, associated to this particular system, play a role of support, but also function as a start or finishing point. The particular case of Quinta de Valverde, is a clear example of how it is possible to collect and store water, even in a harsh, dry location, so that there is not only enough water to supply the region, but to also have an abundance of it, should it be needed. I intend to study and analyse this place and the way the water was collected, stored and transported, as well as its logistics and architecture. This analysis will be made in a theoretical and historical way, but also practical, because beyond the necessary findings, a small intervention in a strategic place will be carried out. This work will allow the social and territorial rehabilitation of the area, with the goal of valorising this national patrimony and, more importantly, allow the constancy of the water line, transforming the current hydraulic system into a re-utilisable, cyclical one.